Review of Printed Electrodes for Flexible Devices - Li, Quanling; Zhang, Jiayan; Li, Qianhao; Li, Guihong; Tian, Xiyue; Luo, Zewei; Qiao, Fei; Wu, Xing; Zhang, Jian (Frontiers in Materials, 2019)
Printed electronic technologies draw tremendous attention worldwide due to their ability to surpass the limitations of traditional high-cost electronics based on rigid silicon and manufacture various devices on flexible substrates. As a critical component of flexible electronics, electrodes fabricated on soft, bendable and stretchable substrates are of great importance. Based on the fabrication process, this paper classifies the mainstream technologies into two categories: top-down and bottom-up. To be specific, the top-down technology includes physical evaporation methods, printing technologies and soft lithography and the bottom-up technology involves polymer-assisted-metal-deposition methods and ion-exchange methods, respectively. In contrast to the top-down technology that transfers the functional ink onto the substrate directly, the bottom-up methods achieve great improvement in the adhesion between the substrates and the metal electrodes. In the end of the paper, the challenges for top-down technologies, including costs, synthesis and choice of ink for printing technologies, the limited choice of metal for bottom-up technologies and the mass production of these methods are also discussed.